Natural Resource-Based Development in Africa Panacea or Pandora's Box? - Andrews, Nathan; Grant, J. Andrew; Ovadia, Jesse Salah (University of Toronto Press, 2022)
There is no question that Africa is endowed with abundant natural resources of different magnitudes. However, more than a decade of high commodity prices and new hydrocarbon discoveries across the continent has led countless international organizations, donor agencies, and non-governmental organizations to devote considerable attention to the potential of natural resource-based development. Natural Resource-Based Development in Africa places a particular emphasis on the actors that help us understand the extent to which resources could be transformed into broader developmental outcomes. Based on a wide variety of primary sources and fieldwork, including in-person interviews and participant observations, this collection contributes to both scholarly and policy discussions around the governance and economic development roles of local entrepreneurs, transnational firms, civil society groups, local communities, and government agencies in Africa's natural resource sectors. Natural Resource-Based Development in Africa explores the impact that these actors have on regional trends such as resource nationalism and local procurement policies as well as grassroots-related issues such as poverty, livelihoods, gender equity, development, and human security.